Epitestosterone and Testosterone have Similar Nonclassical Actions on Membrane of Sertoli Cells in Whole Seminiferous Tubules - de Castro, A. L.; Cavalari, F. C.; Diello, M. V.; Fracasso, B. M.; Loss, E. S. (Hormone and Metabolic Research, 2013)
Epitestosterone is the 17α-epimer of testosterone. This steroid possesses antiandrogenic activities. The mechanism of action of epitestosterone has not been elucidated. The aim of this study was to investigate the nonclassical effect of epitestosterone on the membrane of Sertoli cells in proliferative phase (rats aged 15 days) and in nonproliferative phase (rats aged 21 and 35 days). The membrane potential of Sertoli cells was recorded using a standard single microelectrode technique. Epitestosterone (0.5, 1, and 2 μM) or testosterone (1 μM) was administered alone and after infusion with flutamide (1 μM), verapamil (100 μM), or U-73122 (2 μM). The testes of rats aged 12–15 days were preincubated with 45Ca2+ with or without flutamide (1 μM) and incubated with epitestosterone (1 μM) or testosterone (1 μM). Epitestosterone and testosterone produced a depolarization in the membrane potential and increased the membrane input resistance on Sertoli cells from rats of all 3 ages. The effect of epitestosterone did not change after perfusion with flutamide. Epitestosterone increased 45Ca2+ uptake within 5 min and this effect was not inhibited by flutamide. The absence of an effect by flutamide suggests that epitestosterone acts independently of the intracellular androgen receptor. The depolarizing effect was inhibited by verapamil, a voltage-dependent calcium channel blocker, and by U-73122, a phospholipase C inhibitor. These results indicate that epitestosterone acts on the membrane via a nonclassical signaling pathway; the effect was similar to the testosterone action on membrane of Sertoli cells in whole seminiferous tubules from rat testes.
Keywords: androgens; membrane potential; 45Ca2+ uptake; testis